2017
DOI: 10.4103/aian.aian_492_16
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of carbamazepine in mice

Abstract: Objectives:The aim of this study was to determine the teratogenic effects of carbamazepine (CBZ) in BALB/c mice.Materials and Methods:Mature female and male BALB/c mice (25–30 g) were used for all experiments. After standardization of administration and dose of CBZ, animals in the CBZ-treated groups (CBZ 450 mg/kg and 600 mg/kg) were fed on medicinal diet. The dams in the control group were mated on the same day as that of the CBZ-treated dams. After cesarean section (CS), fetal viability status and weights we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… 3 In addition, studies of prenatal carbamazepine exposure have shown evidence of fetal growth restriction in rodents. 12 , 13 Still, the evidence for an association of fetal growth restriction with prenatal carbamazepine exposure was considered inconclusive before this study, 4 and the risk is not mentioned in the prescribing information for carbamazepine. 24 In two population-based studies based on subsets of data from the current study, prenatal oxcarbazepine exposure was associated with risk of being born SGA, 5 , 25 although fetal growth restriction was not found in a meta-analysis that did not include these two studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 3 In addition, studies of prenatal carbamazepine exposure have shown evidence of fetal growth restriction in rodents. 12 , 13 Still, the evidence for an association of fetal growth restriction with prenatal carbamazepine exposure was considered inconclusive before this study, 4 and the risk is not mentioned in the prescribing information for carbamazepine. 24 In two population-based studies based on subsets of data from the current study, prenatal oxcarbazepine exposure was associated with risk of being born SGA, 5 , 25 although fetal growth restriction was not found in a meta-analysis that did not include these two studies.…”
Section: Discussionmentioning
confidence: 94%
“… 6 , 9 , 10 Chemically, ASMs are heterogeneous drugs that are both related (e.g., oxcarbazepine and carbamazepine) and unrelated (e.g., topiramate and clonazepam). 11 However, in animal studies, prenatal exposure to carbamazepine, 12 , 13 oxarbazepine, 14 clonazepam 15 and topiramate 16 have all been associated with reduced fetal growth. Thus, although animal studies suggest potential harm, the human evidence of some ASMs remains inconclusive.…”
Section: Introductionmentioning
confidence: 99%